2009
DOI: 10.1016/j.syapm.2008.11.006
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas cichorii as the causal agent of midrib rot, an emerging disease of greenhouse-grown butterhead lettuce in Flanders

Abstract: Bacterial midrib rot of greenhouse-grown butterhead lettuce (Lactuca sativa L. var. capitata) is an emerging disease in Flanders (Belgium) and fluorescent pseudomonads are suspected to play an important role in the disease. Isolations from infected lettuces, collected from 14 commercial greenhouses in Flanders, yielded 149 isolates that were characterized polyphasically, which included morphological characteristics, pigmentation, pathogenicity tests by both injection and spraying of lettuce, LOPAT characterist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 44 publications
1
22
0
2
Order By: Relevance
“…Detailed characterization of the genetic variability among isolates belonging to P. viridiflava species was achieved by DNA fingerprinting, based on BOX-and ERIC-PCR (collectively known as rep-PCR) [23]–[25], as was previously discribed [52]. PCR reaction contained 150 ng template DNA, each of the deoxynucleoside triphosphates at a concentration of 250 nM, primers at a total concentration of 2.5 µM, 2.5 mM MgCl 2 , and 2 units of Taq DNA polymerase (Kapa Biosystems) in a total volume of 20 µl.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed characterization of the genetic variability among isolates belonging to P. viridiflava species was achieved by DNA fingerprinting, based on BOX-and ERIC-PCR (collectively known as rep-PCR) [23]–[25], as was previously discribed [52]. PCR reaction contained 150 ng template DNA, each of the deoxynucleoside triphosphates at a concentration of 250 nM, primers at a total concentration of 2.5 µM, 2.5 mM MgCl 2 , and 2 units of Taq DNA polymerase (Kapa Biosystems) in a total volume of 20 µl.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Cottyn et al . () reported that P. cichorii is the causal agent of midrib rot on greenhouse‐grown butterhead lettuce in Belgium and Mirik et al . () isolated P. cichorii from stem and pith necrosis of tomato and leaf spot of the dwarf umbrella tree in Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…The bacterial strains used are listed in Table 1. SF and AF strains were isolated from symptomatic endive and lettuce heads in Belgium as described by Cottyn et al. (2009).…”
Section: Methodsmentioning
confidence: 99%
“…2009) using overhead sprinkler irrigation. This intensive management has been accompanied by the emergence of a new disease termed bacterial midrib rot, caused by Pseudomonas cichorii (Cottyn et al. 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation